Clinical and immunological profile of umbilical involvement in pemphigus vulgaris and pemphigus foliaceus. (22nd October 2012) - Oliveira Júnior, J. V.; Maruta, C. W.; Sousa, J. X; Santi, C. G.; Valente, N. Y. S.; Ichimura, L. M. F.; Périgo, A. M.; Aoki, V.
Summary: Background. Pemphigus vulgaris (PV) and pemphigus foliaceus (PF) are autoimmune vesicobullous disorders with IgG autoantibodies directed against desmoglein (Dsg)1 and 3, which lead to intraepidermal acantholysis. Aim. To characterize the clinical and immunological profile of patients with PF or PV with umbilical involvement. Methods. In total, 10 patients (7 women, 3 men; age range 24–70 years, disease duration 3–16 years) diagnosed with either PV ( n = 5) or mucocutaneous PF ( n = 5) were assessed according to their clinical features, histopathology and immunological findings [direct and indirect immunofluorescence (DIF and IIF) and ELISA with recombinant Dsg1 and Dsg3]. Results. Erythema, erosions, crusts and vegetating skin lesions were the main clinical features of the umbilical region. DIF of the umbilical region gave positive results for intercellular epidermal IgG and C3 deposits in eight patients and for IgG alone in the other two. Indirect immunofluorescence with IgG conjugate showing the typical pemphigus pattern was positive in all 10 patients, with titres varying from 1 : 160 to 1 : 2560. ELISA with recombinant Dsg1 gave scores of 24–266 in PF and 0–270 in PV. Reactivity to recombinant Dsg3 was positive in all five patients with PV (ELISA 22–98) and was negative in all PF sera. Conclusions. All 10 patients with pemphigus with umbilical presentation had the clinical and immunopathological features of either PF or PV. This peculiar presentation, not yet completely elucidated, has rarely been reported in the literature. A possible explanation for this unique presentation may be the presence of either novel epitopes or an association with embryonic or scar tissue located in the umbilical‐cord region.